Analyses of the 2021 Nobel Prize in Physiology or Medicine: Receptors for Temperature and Touch. Issue 1 (2nd January 2022) - Sterner, Elizabeth
ABSTRACT: David Julius, a professor of physiology at the University of California, San Francisco, and Ardem Patapoutian, a molecular biologist at Scripps Research in La Jolla, California, share the 2021 Nobel Prize in Physiology or Medicine for their contributions to the identification of receptors for temperature and touch which are fundamental for an organism's ability to sense and interact with the internal and external environment. The advancement of the molecular understanding of thermosensation and mechanotransduction can further our understanding of the regulation of biological processes. Following a general overview of temperature and touch receptors is a bibliometric analysis of each of this year's laureates and their work.